SELF-ASSESSMENT LEVELS OF CHILDREN FROM LARGE AND SINGLE FAMILIES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The decline in mutual communication in modern families, the lack of spiritual and emotional closeness, the low awareness of parents about the interests, needs, and problems of their children, and the lack of a sense of mutual understanding among family members, in turn, lead to many difficulties in the development of children. This article analyzes the level of self-esteem of children from single and multi-parent families based on B.A. Sosnovsky's "Self-Esteem of the Individual" method.